The revenge of the real politics for a post-pandemic world - Bratton, Benjamin H. 1968- (Verso, 2021)
"COVID-19 exposed the pre-existing conditions of the current global crisis. Many Western states failed to protect their populations, while others were able to suppress the virus only with sweeping social restrictions. "The Revenge of the Real" envisions a new positive biopolitics that recognizes that governance is literally a matter of life and death. Bratton argues that instead of thinking of technology as something that happens to society, we must learn how it can create a politics of infrastructure, knowledge, and direct intervention. In this way, we can build a society based on a new rationality of inclusion, care, and prevention"--
Keywords: Pandemie; COVID-19; Sozialphilosophie; Gesellschaftskritik; Biopolitik; Epidemiology; Epidemics / Social aspects; Epidemics / Political aspects; Communicable diseases / Prevention; COVID-19 (Disease)